The FIAF moving image cataloguing manual - Tadic, Linda (Indiana University Press, 2016)
The FIAF Moving Image Cataloguing Manual' is the result of many years of labor and collaboration with numerous professionals in the moving image field. It addresses the changes in information technology that we?ve seen over the past two decades, and aligns with modern cataloguing and metadata standards and concepts such as FRBR (Functional Requirements for Bibliographic Records), EN 15907, and RDA (Resource Description and Access). The manual is designed to be compatible with a variety of data structures, and provides charts, decision trees, examples, and other tools to help experts and non-experts alike in performing real-world cataloguing of moving image collections.